Diadema mexicanum, a key species of sea urchin in coral reefs of the Eastern Tropical Pacific: state of knowledge and future perspectives. - Alvarado, Juan José (2015)
Diadematids are among the most ecologically important sea urchin families. This review presents the state of knowledge of an important member of that family, Diadema mexicanum, in the Tropical Eastern Pacific based on studies carried out mainly in Panama, Costa Rica and Mexico. Density of D. mexicanum is low, fluctuating between 0.008 and 9.5 ind m-2, however under particular conditions such as El Niño, densities reach up to 150 ind m-2. On the other hand, just one event of mass mortality at a local level has been reported for this species in Mexico. Bioerosion caused by D. mexicanum is more intense in southern reefs, whereas in localities from Mexico values are lower. According to studies carried out in Panama and Mexico it has been determined that D. mexicanum reproduces between April and November and its reproduction is influenced by ocean dynamics of winds and currents. It is necessary to extend the study areas in order to determine if populations of D. mexicanum have a similar behavior along its entire geographical distribution. Finally, it is necessary to assess the effect of extraction for different purposes on this species and identify the actions that should be taken in order to protect its populations.